2016
DOI: 10.3917/spub.163.0391
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs influençant le refus de consulter au centre de santé dans la région rurale Ouest du Burkina Faso

Abstract: Introduction : L’objectif de ce texte est de présenter des logiques qui influencent le refus de se soigner directement au centre de santé, en dehors de l’obstacle financier fréquemment évoqué dans diverses études. Méthodes : L’étude repose sur une enquête ethnographique. Les techniques des entretiens semi-directifs, des observations directes et des entretiens libres (approfondis et centrés sur des récits de vie) ont été mobilisées au cours de cette enquête. Résultats : L’évitement du recours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
11
3
Order By: Relevance
“…A number of studies have found an association between spatial inequalities in access to care and spatial heterogeneity of malaria incidence [42,43]. Yet, contrary to what has been reported elsewhere [44], we failed to found a correlation between the number of malaria cases and the Euclidean distance between villages and their corresponding HC. We used Euclidean distance because it is considered to be the simplest proxy for travel time, which is considered a good measure of access to care.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found an association between spatial inequalities in access to care and spatial heterogeneity of malaria incidence [42,43]. Yet, contrary to what has been reported elsewhere [44], we failed to found a correlation between the number of malaria cases and the Euclidean distance between villages and their corresponding HC. We used Euclidean distance because it is considered to be the simplest proxy for travel time, which is considered a good measure of access to care.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Euclidean distance may not have been the best option, as roads in our study area are in highly variable condition and some become impassable during the rainy season, with some villages left completely isolated. Future studies in the region should use better proxys for travel time in trying to explain the detected hotspots [45].…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas, this is justified by the availability and easy access to medicines and products. Self-medication justifies somewhere a desire for independence and sovereignty [7].…”
Section: Association Of Different Medicinesmentioning
confidence: 99%
“…As much as this disease is "known", it remains lowly controlled by the populations, resulting in very high mortality rates. Indeed, the perceptions of malaria (cause, modes of prevention and treatment) within a given population considerably vary, depending on age, socio-economic level, living environment and level of education [5,6,7]. Questions related to malaria are part of a vast cultural and medical heritage, combining endogenous perception and modern health systems.…”
Section: Introductionmentioning
confidence: 99%
“…Under standard conditions, EBM components generally exhibit columnar microstructures, but by application of these principles to additive technologies, Dehoff et al . were able to obtain site specific control of grain texture in IN718 based on the scan strategy used 3 18 19 . The goal of this work is therefore to use IR thermography to demonstrate the monitoring of grain structure development within an additively manufactured component in order to enable future control systems designed to reliably produce on-demand microstructure control.…”
mentioning
confidence: 99%